Up-scaling mercury emissions from terrestrial surfaces as a response to sustained temperature increase. (15th February 2020) - MacSween, K.; Edwards, G.C.; Howard, D.A.
Abstract: It has been well established that human activities have significantly altered the earth's climate system. Terrestrial Mercury (Hg) emissions exhibit a strong relationship with meteorological variables, in particular solar radiation and temperature. Alterations to these controlling parameters resulting from climate change will influence Hg air-surface exchange trends. Over the past two decades, using the same micrometeorological-based methodology, mercury flux data was collected at a number of varying terrestrial sites globally. This study aimed to investigate the relationship between climate variables and mercury air-surface exchange. The large data set identified significant relationships between Hg air-surface exchange and temperature that was consistent across the multiple field sites, facilitating the development of a well-constrained empirical model to predict the impact of climate change on terrestrial mercury air-surface exchange, with changing temperature. Flux increases calculated, based on IPCC Temperature projections, ranged between 15 and 43% increase for a 1–2 °C rise in temperature by 2050 and 15–96% increase for temperature rise between 1 and 3.7 °C by 2100. The projections developed here indicate that air temperature can be used as a baseline for determining potential terrestrial evasion under projected climate change, prolonging the recovery time of the natural mercury cycle in view of reduced anthropogenic emissions. Highlights: Six mercury flux datasets from terrestrial sites using micrometeorological methods. Identified consistent relationships between Hg surface evasion and air temperature. Empirical model developed to estimate increased Hg evasion with changing temperature. Climate change will potentially prolong recovery time of the global mercury cycle.